On some species of Psalidognathus Gray, especially those of the group “superbus” (Coleoptera, Cerambycidae, Prioninae) - Santos-Silva, Antonio; Spooner, Amoret (Zootaxa, 2021)
The identity of Psalidognathus mygaloides Thomson, 1859 is discussed. The dates of the works in which P. modestus Fries, 1834, P. superbus Fries, 1834, and P. sallei Thomson, 1859 have been described are corrected. The designation of lectotypes for the following species by Quentin & Villiers (1983) is considered to have no nomenclatural value: P. testaceus Thomson, 1877, P. viridiobscurus Thomson, 1877, P. violaceous Thomson, 1877, P. subniger Thomson, 1877, P. ater Thomson, 1877, P. incas Thomson, 1859, P. boucardi Thomson, 1874, P. gloriosus Thomson, 1880, P. sallei, and P. deyrollei Thomson, 1877. A lectotype is designated for P. superbus. Psalidognathus deyrollei is revalidated, and P. sallei is considered a species different from P. friendii Gray, 1831. The following new synonymies are established: P. superbus is a junior synonym of P. friendii; P. victorsinyaevi Lazarev & Marzin, 2019 is a junior synonym of P. rufescens Quentin & Villiers, 1983.